Current evidence on the role of smoking in plastic surgery elective procedures: A systematic review and meta-analysis. Issue 5 (May 2018) - Theocharidis, Vasileios; Katsaros, Ioannis; Sgouromallis, Emmanouil; Serifis, Nikolaos; Boikou, Vasileios; Tasigiorgos, Sotirios; Kokosis, George; Economopoulos, Konstantinos P.
Summary: Background: Smoking is considered to be a significant risk factor for the development of postoperative complications after various surgical procedures, mainly by limiting oxygen delivery to tissues. Evidence on the collective impact of smoking in aesthetic procedure outcomes is scarce. The aim of this study is to evaluate the current evidence on the association between smoking and postoperative outcomes in patients who underwent common elective procedures in plastic surgery. Methods: PubMed and Cochrane bibliographical databases were searched from January 1950 to October 2016 for studies reporting on patients who underwent facelift, abdominoplasty, breast reduction and breast reconstruction and for studies with included data on smoking history of treated patients. Results: Fifty-three studies reporting on postoperative complications in tobacco users undergoing facelift, abdominoplasty, breast reduction and reconstruction were identified. Tobacco use is found to significantly increase the total number of postoperative complications as far as abdominoplasty (OR: 5.43; 95% CI = 2.92–10.10), breast reduction (OR: 2.36; 95% CI = 1.64–3.39) and breast reconstruction (OR: 1.91; 95% CI = 1.69–2.17) are concerned. Smoking history does not significantly affect total postoperative complications after facelift procedures (OR: 3.36; 95% CI = 0.92–12.30). Conclusions: Smoking predisposes to surgical site infections, delayed wound healing and skin necrosis in patients undergoing the most common aesthetic procedures in plastic surgery. More rigorous and detailed reporting on the history of tobacco use and surgical outcomes following plastic surgery procedures is needed to better quantify the impact of smoking on the overall postoperative care for this patient population.